The Role of Good Corporate Governance in Moderating the Effect of Financial Performance on Firm Value: Evidence from Manufacturing Companies Listed on the Indonesia Stock Exchange - Nita Priska Ambarita (LP2M IAIN Palopo, 2026)
-